Comment éviter ou réduire l'exposition des travailleurs au bruit? Guide de bonnes pratiques à caractère non contraignant pour la mise en oeuvre de la directive 2003/10/CE du Parlement européen et du Conseil concernant les prescriptions minimales de sécurité et de santé relatives à l'exposition des travailleurs aux risques dus aux agents physiques (bruit) (Luxembourg, 2009)
"This good practice guide explains how workers' exposure to noise at work can be reduced or avoided. Targeted at Member States, industries and other interested bodies, it describes how to follow Directive 2003/10/EC on the minimum safety and health requirements regarding workers' exposure to the risks arising from noise. In addition, a specific chapter presents practical and specific provisions to help workers and employers in the music and entertainment sectors, where workers are particularly exposed to very high noise levels."